The Effect of Inflammation on Bone - Epsley, Scott; Tadros, Samuel; Farid, Alexander; Kargilis, Daniel; Mehta, Sameer; Rajapakse, Chamith S. (Frontiers in Physiology, 2021)
Bone remodeling is the continual process to renew the adult skeleton through the sequential action of osteoblasts and osteoclasts. Nuclear factor RANK, an osteoclast receptor, and its ligand RANKL, expressed on the surface of osteoblasts, result in coordinated control of bone remodeling. Inflammation, a feature of illness and injury, plays a distinct role in skewing this process toward resorption. It does so via the interaction of inflammatory mediators and their related peptides with osteoblasts and osteoclasts, to alter the expression of RANK and RANKL. Such chemical mediators include TNFa, glucocorticoids, histamine, bradykinin, PGE2, systemic RANKL from immune cells, and interleukins 1 and 6. A thorough understanding of bone response to injury and disease, and ability to detect such biomarkers, as well as imaging to identify early structural and mechanical property changes in bone architecture, is important in improving management and outcomes of bone related pathology. While gut health and vitamin and mineral availability appear vitally important, there are very few intervention strategies currently available to favorably alter bone pathology induced by inflammation. Further research is required in this field to advance early detection and treatments.